Psychological changes and mindfulness-based interventions for cancer survivors - Palao, Ángela; Rodríguez, Beatriz; Priede, Amador; Maeso, Amparo; Arranz, Henar (Psicooncología, 2011)
The population of cancer survivors is increasing due to advances in medicine. Achieving an increase in survival is not enough and the focus is on improving the quality of life in all its dimensions, including psychological and spiritual. New psychosocial needs arise in this population. In general, major mental disorders such as major depression or PTSD are rare among survivors, while less severe adjustment disorders such as depression, anxiety or mixed are relatively common. But not only negative changes in quality of life have been described, there are also several positive psychological changes included in the concept of posttraumatic growth. The similarities between descriptions of change in people experiencing posttraumatic growth and the attitude that Mindfulness promotes suggest that Mindfulness training may promote posttraumatic growth in cancer survivors.
Keywords: Cancer survivor; Posttraumatic growth; Mindfulness